Effect of Surface Mechanical Attrition Treatment on Tribological Behavior of the AZ31 Alloy. Issue 12 (December 2016) - Xia, Shuangwu; Liu, Yong; Fu, Dongming; Jin, Bin; Lu, Jian
Abstract : By surface mechanical attrition treatment (SMAT), a gradient nano structure (GNS) from the surface to center was generated in the AZ31 alloy sheet. The tribological behavior of AZ31 alloy with GNS was systematically investigated by using dry sliding tests, a 3D surface profile-meter and a scanning electron microscope equipped with an energy-dispersive spectrometer. The experimental results indicate that the Mg alloy with GNS exhibits better wear resistance comparing to the as-received sample, which is associated to the alteration of wear mechanism at different sliding speeds. The Mg alloy with GNS presents the wear mechanism of the abrasive wear at 0.05 m/s and the oxidative wear at 0.5 m/s, respectively. Moreover, the GNS can effectively promote the reaction between the oxygen and worn surface, which leads to a compact oxidation layer at 0.5 m/s. The effect of oxidation layer on the wear resistance of the Mg alloy was also discussed.